2013
DOI: 10.1539/joh.12-0266-fs
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis Screening in Japanese Individuals of Working Age and Prejudice against Infected Persons in the Workplace

Abstract: Hepatitis Screening in Japanese Individuals of Working Age and Prejudice against Infected Persons in the Workplace: Nanae SASAKI, et al. Health Promotion Center Shonan Area, Komatsu Ltd.— Background Laboratory confirmation of viral hepatitis infection represents an important issue for working age populations, as early detection and treatment can help ameliorate clinical progression of the disease. On the other hand, prejudice may occur in the workplace against those identified by a positive hepatitis test. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Vietnam has a higher community HIV prevalence rate when compared to Japan (0.5% vs <0.1%) [ 45 ], and additional experiences with HIV care probably bring concomitant increases in knowledge and skills among middle-aged nurses; which may promote their willingness to care for infected patients [ 15 , 46 ]. Although educational strategies clearly represent an appropriate strategy for reducing HIV stigma and discrimination in healthcare practice [ 47 ], our study suggests that the healthcare worker’s age must also be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…Vietnam has a higher community HIV prevalence rate when compared to Japan (0.5% vs <0.1%) [ 45 ], and additional experiences with HIV care probably bring concomitant increases in knowledge and skills among middle-aged nurses; which may promote their willingness to care for infected patients [ 15 , 46 ]. Although educational strategies clearly represent an appropriate strategy for reducing HIV stigma and discrimination in healthcare practice [ 47 ], our study suggests that the healthcare worker’s age must also be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, health checkups are widely accepted opportunities to conduct various screening including for infectious diseases. For example, hepatitis B and C viral screening have been introduced as additional tests during regular health checkups in recent years 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the authors’ knowledge, few if any studies have been conducted in Japan which investigate reluctance to care for HIV, HBV or HCV patients. This is despite the fact that other Japanese researchers have shown that up to 40 % of non-health care workers might harbor a prejudicial perception of HIV and up to 24 % have shown a prejudicial perception of HBV / HCV [ 18 20 ]. The present study aimed, therefore, to determine the factors associated with Japanese nurses’ reluctance to care for patients infected with HIV or HBV / HCV.…”
Section: Introductionmentioning
confidence: 97%